Solitary fibrous tumor of the cerebellopontine angle: A case report and literature review - Joe M. Das; Raj S. Chandran; Rajmohan B. Prabhakar; Anilkumar Peethambaran (Indian Journal of Neurosurgery, 2014)
Solitary fibrous tumors (SFT) are rare dura-based mesenchymal tumors of the central nervous system. SFT occurring in the cerebellopontine (CP) angle is very rare and only 21 cases have been reported in the literature until date. We present a 40-year-old male patient who presented with features of the right-sided facial and acoustic nerves paresis along with same sided cerebellar symptoms of 2 months duration. Magnetic resonance imaging revealed a T2 heterogeneously hyperintense extra-axial lesion, showing intense contrast enhancement in the right CP angle with solid and cystic areas. The lesion was not extending into the internal auditory canal. Digital subtraction angiography showed arterial feeders from vertebro-basilar system. The highly vascular lesion was excised near-totally by suboccipital retrosigmoid craniectomy. The lesion was diagnosed as SFT on histopathological examination and was positive for CD34 and bcl-2.